2015
DOI: 10.1002/ejoc.201500273
|View full text |Cite
|
Sign up to set email alerts
|

Facile, One‐Step Synthesis of 5‐Substituted Thieno[3,4‐c]pyrrole‐4,6‐dione by Palladium‐Catalyzed Carbonylative Amidation

Abstract: Described herein is a facile, one‐step synthesis of 5‐substituted thieno[3,4‐c]pyrrole‐4,6‐diones (TPDs) by a palladium‐catalyzed carbonylative amidation of commercially available dibromoaryl compounds under mild conditions. TPDs are important structural components for organic electronics. Our optimal conditions afforded the desired 5‐n‐octyl‐TPD in a 63 % yield in one step. This is a considerably improved process compared with the most conventional approach (5 steps in 12–22 %) In addition, this method was ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…First, we commenced our study by optimizing an intramolecular transannulation reaction of alkynyl thiadiazole 1a in the presence of a transition-metal catalyst (Table 1). Rh 2 (oct) 4 (5 mol %) and RhCl 3 •H 2 O (5 mol %)/DPPF (12 mol %) were totally ineffective for the transannulation (entries 2 and 3). However, Rh(PPh) 3 Cl and [Ir(COD)Cl] 2 (5 mol % each) in the presence of DPPF (12 mol %) afforded, gratifyingly, the desired transannulated product 2a in 42% and 16% yields, respectively (entries 1 and 5).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we commenced our study by optimizing an intramolecular transannulation reaction of alkynyl thiadiazole 1a in the presence of a transition-metal catalyst (Table 1). Rh 2 (oct) 4 (5 mol %) and RhCl 3 •H 2 O (5 mol %)/DPPF (12 mol %) were totally ineffective for the transannulation (entries 2 and 3). However, Rh(PPh) 3 Cl and [Ir(COD)Cl] 2 (5 mol % each) in the presence of DPPF (12 mol %) afforded, gratifyingly, the desired transannulated product 2a in 42% and 16% yields, respectively (entries 1 and 5).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…For this reason, the development of an efficient synthetic method for functionalized fused thiophenes is highly attractive and poses a significant challenge. To date, various synthetic methods of fused thiophenes from easily available compounds have been reported (Scheme a–g): (a) a one-pot, three-step reaction of 3,4-dibromothiophene using n -BuLi, 1-benzylpiperidin-4-one, CO 2 , and Ac 2 O, (b) basic hydrolysis and subsequent ring closure of a dicarboxylic acid after a Rosenmund–von Braun reaction of 3,4-dibromothiophene, (c) a Pd-catalyzed carbonylative amidation of 3,4-dibromothiophene, (d) a condensation reaction of thiophene dicarbaldehydes and aromatic amines in the presence of 2-mercaptoethanol, (e) Friedel–Crafts acylation of thiophene-3,4-dicarbonyl dichloride and benzene, (f) Suzuki–Miyaura cross-coupling of bromoarylcarboxylate and o -hydroxyarylboronic acid, and (g) reaction of o -hydroxyacetophenone with ethyl cyanoacetate and elemental sulfur under microwave conditions . However, because some of the previously reported synthetic methods demand a strong base, long reaction times, and vigorous reaction conditions, the development of efficient synthetic approaches to overcome these shortcomings has been continuously required.…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, Shinichiro Fuse et al reported the synthesis of TPD through a Pd-catalyzed carbonylative amidation reaction from commercially available 3,4-dibromothiophene in a yield of 63 % (Synthetic route 3). [76] It should be noted it is the most straightforward synthetic route to synthesize TPD by one-step reaction. In 2023, Min et al reported a synthetic route of DT-TPD through a two-step reaction in a yield of 31 %.…”
Section: Imide-functionalized Building Unitsmentioning
confidence: 99%
“…The starting material 1,6,9,10-tetrabromo-perylene monoimide 1 is synthesized from commercially available 3,4,9,10-perylenetetracarboxylic dianhydride ( PTCDA ) by four steps in 37% overall yield according to the literature reported method . Thanks to the relatively higher reactivity in nucleophilic substitution of bromo groups at the bay-region than those at peri positions, compound 2 can be obtained in a yield of 65–70% by heating a solution of compound 1 in N , N -dimethylformamide along with methanol and potassium carbonate at 80 °C for 4 h. , Subsequently, compound 3 can be achieved in a moderate yield by the one-pot palladium-catalyzed domino carbonylative amidation using carbon monoxide as the source of carbonyl in toluene at 100 °C for 10 h . Through the demethylation reaction, compound 4 can be easily obtained in a yield of 56–60% in the liquidated pyridine hydrobromide .…”
mentioning
confidence: 99%